Palmitic Acid: Myths and Reality or Once Again about Features of Fatty Components of Breast Milk Substitutes - O.Yu. Belousova (Zaslavsky O.Yu., 2015)
Palmitic acid is the most prominent fatty acid in breast milk and for that reason fat blends are added into infant formulas that will be converted to palmitic acid in amounts mimicking the amount of that found in human breast milk. But breast milk contains high levels of β-palmitate. There is some evidence that high levels of α-palmitic acid standard mixtures contain (> 20 %) might negatively affect fat and calcium absorption, leading to stool hardness. Therefore most of companies producing highly adapted formulas use palmitic acid not more than 20 %, and some products are enriched with β-palmitate.